2014
DOI: 10.1016/j.urology.2013.09.056
|View full text |Cite
|
Sign up to set email alerts
|

Readmission After Robot-assisted Radical Cystectomy: Outcomes and Predictors at 90-Day Follow-up

Abstract: OBJECTIVE To characterize the outcomes and predictors of readmission after robot-assisted radical cystectomy (RARC) during early (30-day) and late (31–90–day) postoperative periods. METHODS We retrospectively evaluated our prospectively maintained RARC quality assurance database of 272 consecutive patients operated between 2005 and 2012. We evaluated the relationship of readmission with perioperative outcomes and examined possible predictors during the postoperative period. RESULTS Overall 30- and 90-day m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 28 publications
2
43
1
1
Order By: Relevance
“…Most of the surgical series were retrospective, single-center studies, with the exception of some prospective studies [8,9,29,32,33,48,62,63,67,69,71,73,77] and some multi-institutional collaboration papers [19,24,26,30,38,39,43,45,72] (LOE 4). Only three of the comparative studies were randomized [78][79][80] (LOE 2b); all other comparative studies were nonrandomized, whether prospective or retrospective (LOE 4).…”
Section: Quality Of the Studies And Level Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the surgical series were retrospective, single-center studies, with the exception of some prospective studies [8,9,29,32,33,48,62,63,67,69,71,73,77] and some multi-institutional collaboration papers [19,24,26,30,38,39,43,45,72] (LOE 4). Only three of the comparative studies were randomized [78][79][80] (LOE 2b); all other comparative studies were nonrandomized, whether prospective or retrospective (LOE 4).…”
Section: Quality Of the Studies And Level Of Evidencementioning
confidence: 99%
“…Specifically, with regard to series reporting on RARC with mainly extracorporeal conduit diversion, three studies reported on predictors of complications [28,39,43] and one reported on predictors of readmission [48]. …”
Section: Perioperative Outcomes After Robot-assisted Radical Cystectomymentioning
confidence: 99%
“…BMI was not a predictor of mortality and complication development after RC in the Maurer et al 35 study, except for postoperative bleeding, which was more frequent in subjects with a high BMI. Compared to subjects with a BMI of 18-25kg/m 2 , subjects with a BMI >30kg/m 2 had a higher risk of cancer-specific mortality 38,42 , incisional hernia 40 , re-admission 30d and 90d after RC 39 , ileus 36 , parastomal hernia 45 and deep venous thrombosis 43,44 .…”
Section: Body Mass Indexmentioning
confidence: 99%
“…Twelve studies investigated the association between BMI and RC outcomes [33][34][35][36][37][38][39][40][41][42][43][44] . Reyes et al 33 found that tract infections, pyelonephritis, wound infections and overall complications were less frequent in normal-weight patients (18.5-24.9kg/m 2 ) compared to overweight (25-29.9kg/m 2 ) and obese (≥30.0kg/m 2 ) patients.…”
Section: Body Mass Indexmentioning
confidence: 99%
“…Previous studies of radical cystectomies and outpatient urological surgeries found certain patient-level characteristics, including sex and comorbidity, as predictors of readmission. [3][4][5] In 2% to 7% of patients with renal cell carcinoma (RCC), a tumour thrombus may develop that extends into the renal vein and inferior vena cava (IVC). 6,7 In these patients, thrombectomy is routinely performed in conjunction with radical nephrectomy.…”
Section: Introductionmentioning
confidence: 99%